2007
DOI: 10.1186/1475-2875-6-70
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of fosmidomycin monotherapy and combination therapy with clindamycin in the treatment of multidrug resistant falciparum malaria

Abstract: Background: The study investigated the pharmacokinetics of fosmidomycin when given alone and in combination with clindamycin in patients with acute uncomplicated falciparum malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…It is possible that the shorter course of clindamycin used in this study may have insufficiently complemented fosmidomycin and that, as a result, parasite clearance may have been incomplete or delayed. However, neither the good cure rates observed on day 7 (35/37; 94.6%) nor the good results obtained with the F/C combination elsewhere (3,5,6,18,20,23) support this hypothesis, and as previously mentioned, the significantly prolonged parasite clearance times instead support the hypothesis that clindamycin worked better than fosmidomycin. The roles of other partner drugs, such as piperaquine, with longer half-lives and the prospect of requiring shorter dosing courses should be explored.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is possible that the shorter course of clindamycin used in this study may have insufficiently complemented fosmidomycin and that, as a result, parasite clearance may have been incomplete or delayed. However, neither the good cure rates observed on day 7 (35/37; 94.6%) nor the good results obtained with the F/C combination elsewhere (3,5,6,18,20,23) support this hypothesis, and as previously mentioned, the significantly prolonged parasite clearance times instead support the hypothesis that clindamycin worked better than fosmidomycin. The roles of other partner drugs, such as piperaquine, with longer half-lives and the prospect of requiring shorter dosing courses should be explored.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, in vitro synergistic activity between fosmidomycin and clindamycin against various strains of P. falciparum has been demonstrated (27). Different clinical trials have confirmed the safety and efficacy of fosmidomycin alone (15) or combined with clindamycin for the treatment of uncomplicated P. falciparum both in adults (17,18,20,23) and in older children (3,5,6,20). However, data on the efficacy of this combination in younger children, the age group most affected by malaria worldwide, are scarce.…”
mentioning
confidence: 99%
“…Due to its short half-life in plasma, FOS is not suitable for monotherapy; however, combination therapy studies in humans revealed success in maintaining total parasite clearance when FOS was used with artesunate or clindamycin (37)(38)(39)(40)(41)(42)(43). Thus far, our results indicate that MMV008138 affects apicoplast function and that its molecular target may differ from current antiapicoplast drugs, like FOS.…”
Section: Discussionmentioning
confidence: 78%
“…Compounds 4, 9 and 15 (fosmidomycin) exhibited low BBB penetration due to their negative logD values (À0.423, À0.404 and À2.244, respectively). However, there are some reports of headache and vertigo from Fosmidomycin mono-therapy to patients and these adverse effects are considered due to its MW (<300 Da) and some amount of fosmidomycin molecule squeezing along the gap junctions of BBB (Na-Bangchang et al 2007;Meyers 2008).…”
Section: Computational Pharmacokinetic Studiesmentioning
confidence: 99%
“…Similarly, the highest log D value possessed by the lead compound 1 > 8 > 6 >13 also conferred them to be released metabolically via bile canaliculi and faecal route (Smith et al 1996). Fosmidomycin will be released solely by the renal clearance due to MW less than 250 Da (Na-Bangchang et al 2007). …”
Section: Computational Pharmacokinetic Studiesmentioning
confidence: 99%